Empowerment of women's â€œmeronceâ€ crafts by through on-line marketing strategy in order to increase the income of the family in the village of Merawan Dolok, Dolok Merawan village, Serdang Bedagai district, North Sumatera - Badaruddin; Erika Revida; Lina Sudarwati (Talenta Publisher, 2019)
The